Modernizing the education workforce: A perspective from Scotland - Ozga, J (2005)
This article argues that there are global pressures for modernization of the education workforce that produce broadly similar policy responses and pressures on the teaching profession. It suggests, however that these 'travelling' policies are mediated by the 'embedded' practices and cultures of different systems to produce particular 'local' versions of policy. These contribute to tension between decontextualized agendas for modernization and embedded practices and cultures. Recent policy developments in work organizations pay, professional development and career progression for the teaching profession may provide illuminating examples of the coexistence of 'travelling' UK policy and 'embedded' (Scottish) policy and may also provide evidence of growing policy divergence. Such inter-UK policy divergence is significant in itself and also helps to identify the circumstances and resources that sustain mediation of, or resistance to, 'travelling' policy in education.